Mutations in the U5 Sequences Adjacent to the Primer Binding Site Do Not Affect tRNA Cleavage by Rous Sarcoma Virus RNase H but Do Cause Aberrant Integrations In Vivo - Oh, Jangsuk (American Society for Microbiology, 2006)
In most retroviruses, the first nucleotide added to the tRNA primer becomes the right end of the U5 region in the right long terminal repeat (LTR); the removal of this tRNA primer by RNase H defines the right end of the linear double-stranded DNA. Most retroviruses have two nucleotides between the 5′ end of the primer binding site (PBS) and the CA dinucleotide that will become the end of the integrated provirus. However, human immunodeficiency virus type 1 (HIV-1) has only one nucleotide at this position, and HIV-2 has three nucleotides. We changed the two nucleotides (TT) between the PBS and the CA dinucleotide of the Rous sarcoma virus (RSV)-derived vector RSVP(A)Z to match the HIV-1 sequence (G) and the HIV-2 sequence (GGT), and we changed the CA dinucleotide to TC. In all three mutants, RNase H removes the entire tRNA primer. Sequence analysis of RSVP(HIV2) proviruses suggests that RSV integrase can remove three nucleotides from the U5 LTR terminus of the linear viral DNA during integration, although this mutation significantly reduced virus titer, suggesting that removing three nucleotides is inefficient. However, the results obtained with RSVP(HIV1) and RSVP(CATC) show that RSV integrase can process and integrate the normal U3 LTR terminus of a linear DNA independently of an aberrant U5 LTR terminus. The aberrant end can then be joined to the host DNA by unusual processes that do not involve the conserved CA dinucleotide. These unusual events generate either large duplications or, less frequently, deletions in the host genomic DNA instead of the normal 5- to 6-base duplications.